Holistic Health, Disadvantage, Higher Education Access and Success: A Reflection (Journal of Student Affairs in Africa, 2021)
The objective of this article is to reflect upon the relationships amongst health, disadvantage, educational opportunities, and higher education access and success. This is a reflective article taken from the literature review of a doctoral study on the relationship between health, access to, and success within, higher education. The importance of health in education and the practical implementation of programmes resulting in enhanced health and academic success amongst higher education students is reviewed. Literature for the doctoral study on which this reflection was based was sourced predominantly from Pub-Med Central, the U.S. National Institute of Health National Library of Medicine and The South African South-East Academic Library Services. From this discussion, the rationale for a holistic health promotion programme within the higher education setting, for students from socioeconomically deprived backgrounds, is given. The problem of educational failure of students from socioeconomically disadvantaged backgrounds in higher education could be lessened by instituting a holistic health promotion programme within the first year of study. Evidence suggests that such a programme would have both health and educational advantages.
Keywords: disadvantage; health; higher education; holistic health promotion; student success